Case Report: Blinatumomab as upfront consolidation and maintenance therapy in a pediatric patient with high-risk B-cell acute lymphoblastic leukemia - Gupta, Sumit; Casey, Jessica; Lasky, Joseph (Frontiers in Oncology, 2023)
B-cell acute lymphoblastic leukemia (B-ALL) is the most common malignancy in children. The current conventional chemotherapy regimens have high overall survival but with significant short- and long-term toxicities, sometimes requiring delay and termination of chemotherapy. Bispecific T-cell engager antibody blinatumomab has been successful in achieving bone marrow remission and acting as bridging therapy in minimal residual disease (MRD) positive relapsed adult and pediatric B-ALL patients. Its role as upfront therapy is being explored. Here, we report the first case to our knowledge showing the feasibility, tolerability, and sustained remission using blinatumomab upfront as consolidation and maintenance therapy for two years in a pediatric patient with high-risk B-ALL who had significant toxicities with conventional chemotherapy. An 11-year-old Hispanic female presented with complaints of fever, abdominal pain, and fatigue. On further evaluation, she had tachycardia, pallor, cervical lymphadenopathy, and pancytopenia. Bone marrow studies confirmed high-risk B-ALL. The patient was started on induction chemotherapy per AALL1131. Her induction course was complicated by syncope, febrile neutropenia, and invasive cryptococcal fungal infection. End of induction bone marrow results were MRD negative. Further chemotherapy was withheld due to cardiopulmonary and renal failure, along with ventricular arrhythmias requiring intensive care. The patient received two cycles of blinatumomab as consolidation therapy and then transitioned back to conventional consolidation therapy; however, it was terminated mid-consolidation due to pseudomonas and aspergillus sepsis. She was then given blinatumomab maintenance therapy for two years and tolerated it well without any irreversible toxicity. She had an episode of staphylococcus epidermidis sepsis and pneumonia treated by antibiotics and a single episode of a seizure while on blinatumomab therapy. At the time of publication, she is 25 months off treatment and in sustained remission without any further transplant or chemotherapy. She received monthly intravenous immunoglobulin G during the blinatumomab maintenance. Blinatumomab given upfront as consolidation and maintenance therapy for two years in a pediatric high-risk B-ALL patient with significant toxicities to conventional chemotherapy was feasible and very well tolerated without any irreversible toxicity and led to sustained remission without any bridging transplant or further chemotherapy.